TEMPORAL AND SPATIAL FLUCTUATIONS OF WARMING IN ANTARCTICA AND THE ATMOSPHERIC CIRCULATION - エノモト, ヒロユキ; ENOMOTO, Hiroyuki (National Institute of Polar Research, 1997)
P(論文) An abrupt and extreme warming was observed in the mid-winter season, in June 1994. The air temperature increased from -72℃ to -36℃ in two days. This warming caused reduced cooling of air temperature in the winter and hence resulted in increase of the temperature throughout a month. The area of warming and its temperature change were analyzed by using the passive microwave radiometer (DMSP SSM/I) data. This area appeared first in the coastal region around the Lambert Glacier, East Antarctica and expanded to the inland areas over Dome Fuji, then diminished over the Dome C area. The weather chart showed a high pressure area over East Antarctica, and advection of air from the coastal region to the inland areas of Antarctica. A blocking of high pressure was detected in the higher troposphere and persisted for several weeks. The seasonal variations of the polar vortex in the stratosphere (30hPa) showed a westward shift of the center area in the corresponding period. This event is important to understand the Antarctic climate and also exchange processes of polar air masses. departmental bulletin paper